Study on Degenerate Stirling Numbers (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we consider various Stirling numbers of both kinds, including the unsigned degenerate Stirling numbers of the first kind, the degenerate Stirling numbers of the second kind, the unsigned degenerate r-Stirling numbers of the first kind and the degenerate r-Stirling numbers of the second kind. The aim of this paper is by using generating functions to further study explicit expressions, some identities and equivalent relations for those Stirling numbers.
Keywords: unsigned degenerate Stirling numbers of the first kind; unsigned degenerate r-Stirling numbers of the first kind; degenerate Stirling numbers of the second kind; degenerate r-Stirling numbers of the second kind